Cophylogeny, narrow host breadth and local conditions drive highly specialized bird-haemosporidian associations in West-Central African sky islands - Bodawatta, Kasun H; Albrecht, Tomáš; Krausová, Simona; Nana, Eric Djomo; Hořák, David; Sedláček, Ondřej; Jønsson, Knud A; Munclinger, Pavel (Proceedings. Biological sciences, 2025)
The parasite island syndrome denotes shifts in parasite life histories on islands, which affect parasite diversity, prevalence and specificity. However, current evidence of parasite island syndromes mainly stems from oceanic islands, while sky islands (i.e. mountains isolated by surrounding low-elevation habitats) have received limited attention. To explore the parasite syndrome in Afrotropical sky islands, we examined haemosporidian blood parasites and their bird hosts in two Afromontane regions in Cameroon. Analysing more than 1300 bird blood samples from the Bamenda Highlands and Mount Cameroon, we found considerably reduced parasite lineage diversity and total prevalence in Mt Cameroon, but not in the Bamenda Highlands. We found highly specific parasite-host interactions at both sites and these associations showed significant phylogenetic congruence, suggesting that closely related parasites infect phylogenetically related hosts. These parasite-host associations tend to be shaped mainly by duplications, switches, losses and failures to diverge rather than through co-speciation events. Overall, the high specificity and parasite-host association differences at local scales largely agree with the limited insights from other sky islands. Yet the drivers of these interactions differ geographically, suggesting that unique dynamics of fragmentation and isolation of montane habitats can lead to similar patterns of host-parasite interactions that are shaped by different underlying drivers.
Keywords: Haemosporida; avian malaria; Cameroon; parasite island syndrome; Bird Diseases; Birds; Islands; protozoální infekce zvířat; parasite–host networks; Kamerun; Protozoan Infections, Animal; taxon cycles; nemoci ptáků; zvířata; Host Specificity; fylogeneze; Host-Parasite Interactions; ostrovy; interakce hostitele a parazita; ptáci; Phylogeny; hostitelská specificita; Animals